Behavioural Ecology And Conservation Management Of Dusky Langurs (Trachypithecus Obscurus) In Penang, Malaysia - Yap, Jo Leen (2022)
In this study, the activity budget, habitat use, and diet of four habituated study groups in different habitat types in Penang were assessed to better understand how langurs behave in anthropogenic environments. This study was conducted between January 2016 and December 2019 using behavioural sampling techniques such as scan, focal sampling, vegetation plotting, home range assessment, and camera trapping.